Rural school students attitudes toward reading english materials and their perceptions how reading can help them in their studies : a survey on lower secondary school students of SMK Tutoh Apoh, Baram - Puyang, Jok (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study is to gather information pertaining reading attitudes among Lower Secondary rural school students at SMK TUTOH APOH in Baram. The objectives of the study is to examined what types of non-academic and academic reading materials students like to read, and how often they read, what are students feelings toward reading and their perceptions how reading can help them in their studies. A set of 150 questionnaires was administered to a group of 150 rural students who made up the samples of the study. The results wi ll be analyzed based on empirical studies. The findings of the study revealed that majority of the respondents' demonstrated positive attitudes toward reading the English materials such as Magazines, Comics, Adventure, Horror, School Text Books, Reference Books, Literature. The findings revealed that reading has helped them to acquire knowledge, to pass the examination and school projects. Many factors affect students attitudes toward reading such as their personal experiences with reading, family background, school environment, lack of reading resources and geographical isolation make them inaccessibility to the reading materials. The findings of the survey will also help to raise awareness among all parties about crucial problems in the rural school settings.